1999
DOI: 10.1038/emm.1999.32
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of recombinant murine endostatin in E. coli

Abstract: Endostatin, a carboxyl-terminal fragment of collagen XVIII is known as an anti-angiogenic agent, that specifically inhibits the proliferation of endothelial cell and the growth of several primary tumor. We report here the purification and characterization of the recombinant murine endostatin (rmEndostatin) which was expressed in a prokaryotic expression system. This rmEndostatin has similar physiochemical properties of yeast-produced recombinant endostatin, and it also specifically inhibits the proliferation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…This protein was comparable to the one obtained from the use of Yeast-expression system in physiochemical properties and also in anti-angiogenic activities. 81 In another study, production of soluble recombinant murine endostatin was the main aim of study. A purification method was developed by Huang et al in order to production of an effective and soluble rEs.…”
Section: Clinical Application Challengesmentioning
confidence: 99%
“…This protein was comparable to the one obtained from the use of Yeast-expression system in physiochemical properties and also in anti-angiogenic activities. 81 In another study, production of soluble recombinant murine endostatin was the main aim of study. A purification method was developed by Huang et al in order to production of an effective and soluble rEs.…”
Section: Clinical Application Challengesmentioning
confidence: 99%
“…Brooks' group generated similar NC1 fragments and described the anti-angiogenic effects of α2, α3 and α6 NC1 in chorioallantoic membrane (CAM) assays (Petitclerc et al, 2000). However, none of these NC1 fragments Yamaguchi et al, 1999;You et al, 1999;Taddei et al, 1999;Dhanabal et al, 1999a) Tumor regression (O'Reilly et al, 1997;Boehm Tumor angiogenesis (O'Reilly et al, 1997;Boehm et al, et al, 1997) 1997; Bergers et al, 1999;Blezinger et al, 1999;Boehle et al, 2001;Dhanabel et al, 1999b;Kisker et al, 2001;Sorensen et al, 2002;Yoon et al, 1999) Down-regulation of gene transcription (Shirichi Choroidal neovascularization ) and Hirata, 2001;Hanai et al, 2002) G1 arrest of endothelial cells (Hanai et al, 2002) Arthritis (Matsuno et al, 2002;Yin et al, 2002) In vitro stabilization of microvessels (Ergun et Microvessel formation in rat aortic or human vein ring al., 2001) angiogenesis assay Ergun et al, 2001) Chorioallantoic membrane angiogenesis FGF2-induced Migration of neural and non-neural cells in C. elegans ) Migration and branching morphogenesis of renal epithelial cells ) FAK phosphorylation, focal adhesion and actin stress fibers formation growth factor induced (Dixelius et al, 2002;Wickstrom et al, 2001) Endothelial and cancer cell invasion through Matrigel (Kim et al, 2000) Immobilized monomeric…”
Section: Biological Functions Of Nc1 Fragments In Angiogenesis and Tumentioning
confidence: 99%
“…In vitro, endostatin inhibits basal and FGF2 or VEGF-induced proliferation and migration of different endothelial cell types (Dhanabal et al, 1999b;O'Reilly et al, 1997;Taddei et al, 1999;Yamaguchi et al, 1999;You et al, 1999). The circulating form purified from human plasma lacks 12 N-terminal residues and does not inhibit proliferation (Standker et al, 1997); so the antiproliferative activity of endostatin requires the full-length fragment but is independent of its zinc-or heparin-binding Roles for non-collagenous domains of collagens capacity (Yamaguchi et al, 1999).…”
Section: Nc1(xv) Nc1(xviii) Endostatin and Endostatin-like Fragmentsmentioning
confidence: 99%
“…Several studies on the refolding of endostatin have been reported during the past decade (21,22). To evaluate whether or not endostatin is correctly refolded, several key criteria should be employed, such as sodium dodecylsulfate polyacrylamide gel electrophoresis (SDS-PAGE), high performance liquid chromatography (HPLC), circular dichroism (CD), Tryptophan emission fluorescence (Trp FL), nuclear magnetic resonance (NMR), and activity assay.…”
Section: Criteria To Assure Correct Folding Of Endostatinmentioning
confidence: 99%